A Time Series Observation of Chinese Children Undergoing Rigid Bronchoscopy for an Inhaled Foreign Body: 3149 Cases in 1991-2010 - Xu Zhang; Wen-Xian Li; Yi-Rong Cai (Chinese Medical Journal, 2015)
Background: In China, tracheobronchial foreign body (TFB) aspiration, a major cause of emergency episode and accident death in children, remains a challenge for anesthetic management. Here, we share our experience and discuss the anesthetic consideration and management of patients with TFB aspiration. Methods: This was a single-institution retrospective study in children with an inhaled foreign body between 1991 and 2010 that focused on the complications following rigid bronchoscopy (RB). Data including the clinical characteristics of patients and TFB, anesthetic method, and postoperative severe complications were analyzed by different periods. Results: During the 20-year study period, the charts of 3149 patients who underwent RB for suspected inhaled TFB were reviewed. There were 2079 male and 1070 female patients (1.94:1). A nut (84%) was the most commonly inhaled object. The study revealed a 9% (n = 284) overall rate of severe postoperative complications related to severe hypoxemia, laryngeal edema, complete laryngospasm, pneumothorax, total segmental atelectasis, and death with incidences of 3.2%, 0.9%, 1.3%, 0.3%, 0.3%, and 0.1%, respectively. The rates of preoperative airway impairment, negative findings of TFB, and adverse postoperative events have been on the rise in the past 5 years. Conclusions: The survey results confirmed that hypoxemia remains the most common postoperative complication in different periods. Both controlled ventilation and spontaneous ventilation were effective during the RB extraction of the foreign body at our hospital in the modern technique period. An active respiratory symptom was commonly seen in the groups with negative findings.